Synergetic synthesis of optimal control laws for nonlinear dynamic objects - A. Stenin; V. Pasko; M. Soldatova; І. Drozdovich; S. Stenin (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
The nonlinearity of a fairly large class of real technical objects is a significant obstacle in the development of control systems for them. In particular, the synthesis of optimal control laws for nonlinear dynamic objects is a very complex task, which often cannot be solved in an analytical form. This article discusses a synergetic approach to solving problems of synthesizing optimal control systems for one class of nonlinear objects. The synergetic synthesis of optimal stabilizing control laws for one class of nonlinear dynamic objects proposed in the article is based on the joint use of the well-known AKOR method and a specially designed synergetic functional. Synergetic synthesis of optimal stabilizing control laws based on the AKOR method and a specially designed synergetic functional that meets the conditions formulated in the article allows, on the one hand, to ensure asymptotic stability and, on the other hand, to ensure the specified dynamic properties of transient processes for one class of nonlinear dynamic systems. The practical implementation of this approach is demonstrated using the example of the synergetic synthesis of the law of optimal stabilization given in the article.